A Hemi-nested, Allele Specific, Whole Blood PCR Assay for the Detection of the Factor V Leiden Mutation - Sinclair, Gary D; Low, Sandra; Poon, Man-Chiu (Thrombosis and Haemostasis, 1997)
We describe a novel hemi-nested, allele specific whole blood PCR assay for detection of the factor V Leiden mutation associated with the plasma defect, activated protein C resistance. This assay utilizes 5 μl of whole blood without prior DNA extraction. The hemi-nested design, employing an outer primer pair in combination with nested, allele specific primers obviates the need for restriction enzyme digestion. PCR reactions are analysed directly on agarose or polyacrylamide minigels. The assay confirmed the genotypes of 50 individuals previously categorized by PCR and Mnll digestion, and has been subsequently utilized in the genotyping of 445 individuals referred for thrombosis studies.